REHYDRATION KINETICS OF MICROWAVE-DRIED OKRAS AS AFFECTED BY DRYING CONDITIONS - Apar, Dilek Kilic; Demirhan, Elcin; Ozbek, Belma; Dadali, Goekce (WILEY-BLACKWELL, 2009)
The aim of the present work was to understand the effect of drying conditions (microwave output powers and sample amounts) and rehydration temperature on rehydration kinetics of microwave-dried okras. Four different models, Peleg's, Weibull, first order and exponential association, were applied to experimental data, and the corresponding parameters of the models were obtained. In addition, the kinetic parameters of the models were correlated with the ratio of microwave output power to sample amount and temperature. Although all the models applied provided a good agreement with the experimental data with high values of the coefficient of determination of R(2), the first-order kinetic model was chosen as the appropriate model because of its simplicity. By using the kinetic parameters of this model, the activation energy for rehydration kinetics was estimated as 1.15 kJ/mol.
Keywords: WATER-ABSORPTION; QUALITY CHANGES; MOISTURE UPTAKE; DEHYDRATION; OPTIMIZATION; TEMPERATURES; EQUATION; SOAKING; COWPEA; CEREAL; Food Science & Technology